ANALYSIS OF STORAGE SYSYTEM INFLUENCE ON ENERGY LOSSES IN POWER SYSTEM (Part 1) - A. M. Golubev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes methodology  for evaluation of storage  system influence on energy losses. The methodology makes it possible to investigate  influence of some operational modes of devices on energy losses for a wide range of variants pertaining to reset conditions. The paper provides mathematical dependences that determine criteria for maximization of energy loss reduction.